Vertical Integration, Competition and Financial Exchanges: Is there Grain in the Silo? - Steffen Juranek; Uwe Walz (Verein für Socialpolitik, 2010)
This paper aims to contribute to the ongoing discussion on horizontal vs. vertical integration as further development path in the financial security service industry, consisting of trading, clearing and settlement. Using a stylized model of the industry we investigate the incentives to vertically or horizontal integrate from the individual firm's point of view as well as its consequences on competition and welfare. Our analysis reveals that the incentives to vertically integrate crucially depend on industry and market characteristics such as the degree of differentiation and integration of trading platforms as well as the role liquidity effects play for traders. Furthermore, we show that market forces may suffer from a coordination problem resulting from historical conditions and ending in vertically integrated structures which are not in the interest of the firms. Comparing horizontal with vertical integration, we find a potential tendency for excessive vertical integration, a problem which can be addressed by policy measures such as the Target 2 securities program.
Keywords: G15; L13; L22; 330; vertical and horizontal integration; competition; trading; settlement